2018
DOI: 10.2147/ott.s166653
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of fulvestrant plus a targeted agent with fulvestrant alone in hormone receptor-positive advanced breast cancer that progressed on prior endocrine therapy: a meta-analysis

Abstract: Fulvestrant is recommended for the hormone receptor-positive metastatic breast cancer (MBC) patients progressed during or after prior endocrine therapy. Notably, recent evidence has also demonstrated that adding a targeted agent to fulvestrant conferred a significantly clinical benefit in these patients. Since these results were inconsistent among the studies, this meta-analysis herein was conducted to compare the efficacy and toxicities of the fulvestrant-based combination therapy with fulvestrant monotherapy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
7
0
Order By: Relevance
“…Although a number of studies have shown that CDK4/6 inhibitors added to ET is associated with a significant increase in PFS, OS of patients undergoing this treatment is unclear. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Several recent randomized clinical trials have shown that treatment with CDK4/6 inhibitors and ET compared with ET alone increased OS among patients with HR-positive, ERBB2 -negative metastatic breast cancer. 22 , 23 , 24 , 25 , 26 However, other randomized clinical trials have found that treatment of patients with HR-positive, ERBB2 -negative metastatic breast cancer with CDK4/6 inhibitors and ET, compared with ET alone, does not prolong OS.…”
Section: Introductionmentioning
confidence: 99%
“…Although a number of studies have shown that CDK4/6 inhibitors added to ET is associated with a significant increase in PFS, OS of patients undergoing this treatment is unclear. 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 Several recent randomized clinical trials have shown that treatment with CDK4/6 inhibitors and ET compared with ET alone increased OS among patients with HR-positive, ERBB2 -negative metastatic breast cancer. 22 , 23 , 24 , 25 , 26 However, other randomized clinical trials have found that treatment of patients with HR-positive, ERBB2 -negative metastatic breast cancer with CDK4/6 inhibitors and ET, compared with ET alone, does not prolong OS.…”
Section: Introductionmentioning
confidence: 99%
“…Extracted information are as following: 1) first author' name, year of publication, origin country, tumor type, sample size, follow-up months, cut-off value, clinical TNM stage, detection and survival analysis method; 2) HRs or ORs with 95% CI of BCAR4 for overall survival (OS), progression-free survival (PFS), DFS, recurrence-free survival (RFS), lymph node metastasis (LNM) and distant metastasis (DM). If only Kaplan-Meier curves were provided in certain studies, the survival rates were indirectly extracted from the graphical plots and calculated HRs with 95% CIs were determined by using Engauge Digitizer software (Version 4.1) as previously described 35. Moreover, best efforts were made by contacting the corresponding author to obtaining the possible data if they were not available from the enrolled articles.…”
Section: Methodsmentioning
confidence: 99%
“…If data of interest were not accessible, we obtained the missing data by contacting the corresponding author of enrolled articles. If only Kaplan-Meier (K–M) curves were provided in some studies, we used the Engauge Digitizer (Version 4.1) to calculate the pooled HRs and 95% CIs through indirect extraction from the plots [33].…”
Section: Methodsmentioning
confidence: 99%